The Concept of Al-‘Imarah in the Qur’an and Its Relevance to Mosque Prosperity (A Tafsir Study of Qur’an Surah At-Tawbah verse 18) - Mufarrochah Mufarrochah; Amir Mahmud; Nyoko Adi Kuswoyo; Mukhid Mashuri (Mauriduna : Journal of Islamic Studies, 2026)
This study examines the concept of Al-‘Imārah in the Qur’an and its relevance to the prosperity of mosques by focusing on the interpretation of Surah At-Taubah verse 18. This study employs a qualitative approach with a library research method and applies the thematic interpretation method (tafsir maudhu‘i). The primary data sources include the Qur’an and classical and contemporary kafir literature, such as Tafsir Ibn Kathir and Tafsir Al-Misbah. The results show that the concept of Al-‘Imārah in the Qur’an is not limited to the physical construction of mosques but also includes spiritual, social, and civilizational prosperity. The spiritual dimension is manifested through various forms of worship, such as congregational prayer, dhikr, and Qur’anic recitation. The social dimension is reflected in the mosque’s function as a center for social activities, including zakat distribution, charity, and community solidarity strengthening. Meanwhile, the civilizational dimension is demonstrated by the mosque’s role as a center for education and community development. In the modern context, the concept of Al-‘Imārah remains highly relevant in revitalizing the mosque’s role as a center of spiritual development, education, and community empowerment. Therefore, the prosperity of mosques should be holistically understood so that they can function as centers for spiritual, social, and civilizational development in Muslim societies.